Cell and developmental biology - a shared past, an intertwined future. - Dawes-Hoang, R.E.; Wieschaus, E.F. (Developmental Cell, 2001)
Cell and developmental biology are distinct disciplines with clear differences in emphasis and domains of interest, yet they also share a common historic origin and benefit from an increasingly productive exchange of insights and influences. Our goal in this commentary is to examine the common origin of cell and developmental biology, to explore ways in which they currently interact, and to consider the connections and differences that exist between these two fields.